Pharmacoepidemiological profile and polypharmacy indicators in elderly outpatients - André de Oliveira Baldoni; Lorena Rocha Ayres; Edson Zangiacomi Martinez; Nathalie de Lourdes Sousa Dewulf; Vânia dos Santos; Paulo Roque Obreli-Neto; Leonardo Régis Leira Pereira (Universidade de São Paulo, 2013)
This cross-sectional study was carried out with 1000 elderly outpatients assisted by a Basic Health District Unit (UBDS) from the Brazilian Public Health System (SUS) in the municipality of Ribeirão Preto. We analyzed the clinical, socioeconomic and pharmacoepidemiological profile of the elderly patients in order to identify factors associated with polypharmacy amongst this population. We used a truncated negative binomial model to examine the association of polypharmacy with the independent variables of the study. The software SAS was used for the statistical analysis and the significance level adopted was 0.05. The most prevalent drugs were those for the cardiovascular system (83.4%). There was a mean use of seven drugs per patient and 47.9% of the interviewees used >7 drugs. The variables that showed association with polypharmacy (P value < 0.01) were female gender, age >75 years, self-medication, number of health problems, number of medical appointments, presence of adverse drug events, use of over-the-counter drugs, use of psychotropic drugs, lack of physical exercise and use of sweeteners. The exposition to all these factors justified the high prevalence of polypharmacy amongst the interviewees. These results showed the need to adopt clinical intervention and educational and managerial measures to analyze and promote rationality in the use of drugs amongst the elderly users of SUS.